Pendampingan Budidaya Tikus Hutan Ekor Putih Pada Pemburu Tikus Desa Ampreng Kecamatan Langowan Kabupaten Minahasa - Laatung, Sylvia; Ransaleleh, Tiltje; Lapian , Hapry; Onibala , Jane (The Studies of Social Sciences, 2024)
ABSTRACT The white-tailed forest rat is a type of rat that is consumed by some Minahasa people, especially on holidays or especially for families. In almost all Minahasa traditional markets you can find rats being sold for IDR 100,000 per three heads. This shows that the animal has sale value. Therefore, the Hope and Endemic Animal Laboratory Team will carry out activities to assist rat cultivation for rat hunters so that they can get rats without having to hunt. Mentoring activities will be carried out for 6 months targeting the rat hunting group in Ampreng Langowan Village. This activity was carried out using the Focus Group Discussion method, lectures and practice at the location involving 10 rat hunters. Topics of discussion are about making cages, providing food, maintaining cages. The activity implementation time is 6 (six) months with preparation stages (preparing location, materials, feed), implementation (Focus Group Discussion, lectures, and practice), publication, preparation of wishes, and reporting. The result of this activity is that ten hunters have been able to implement cultivation well and correctly and obtain economic benefits so as to support food security and independence.